(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Internet memes, deployed for various purposes during the Nigerian 2015 presidential election, manifested in different media, including Nairaland Forum. Existing studies on 2015 presidential elections focused on campaign strategies, hate speech-related issues and socio-linguistic features, paying little attention to the use of Internet memes in projecting issues raised by the election. Therefore, this study investigates the deployment of Internet memes in the discourse on Nigeria’s 2015 presidential election on Nairaland Forum, to determine the contexts evoked. Kress and van Leeuwen’s Multimodal Theory and Mey’s Pragmatic Acts Theory was adopted. 12 out of 24 data samples were purposively selected for analysis. The contexts evoked includes the historical-religious context referring to history and religion as solutions to the leadership problems of the country. The war context depicted violence as a recurring feature in Nigeria’s election. While the educational context exposed the inadequacies of a candidate’s academic qualifications; the economic context exposed the country’s economy. The sporting context engaged showed the electoral process as a competition; whereas the socio-political context projected the electorate’s involvement and enthusiasm during and after the election. Verbal and non-verbal modes were identified to include text structures, colour and gaze. They form the basis for the communication and comprehension of the relevance of the Internet memes, hence, projecting how memes can be deployed to project the state of affairs of a nation during elections. Keywords: , , , ,